The use of lidar images in Costa Rica: Case studies aplied in geology, enginneering, and archeology - Ruíz, Paulo (2014)
We present a review about lidar technology evolution, it´s improvements and additions from other technologies in the last 15 years. Also, we show data regarding the operation of aerial and terrestrial lídar equipment, technical parameters for data acquisition and examples from different data resolutions. We present the results from four case studies in Costa Rica: 1) the finding of pre-hispanic trials near Arenal volcano. 2) A case of geologic mapping and the finding of new volcanic structures in the north flank of Poás volcano. 3) The characterization of a landslide near Palmares that represents a hazard for the road network and 4) a detail survey of a pre-hispanic stone sphere. In the following years, the results from new lídar studies (terrestrial, aerial and/or both) will become more frequent, because its cost will be more affordable, and the transference of data between institutions will generate new applications in different research fields